Satisfaction or Hard Labour? Portrait of a Ballet School in 52 Percent by Rafał Skalski - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
How is ballet presented in documentaries? Is Central European cinema different from cinema in the West in this respect? 52 Percent, Rafał Skalski’s documentary about Alla, a girl dreaming of becoming a ballerina, provides an intriguing answer to this question. Th is article compares 52 Percent by Rafał Skalski with two documentaries made in the West (First Position and Only When I Dance), which also show the endeavours of young people who want to fulfil their dreams of becoming ballet dancers. Alla tries to enrol in the famous Russian Agrippina Vaganova Academy of Russian Ballet in Sankt Petersburg. Th e exams are really tough, and she must do additional exercises to lengthen her legs (she lacks 0.4% to achieve the perfect leg-upper body ratio). The girl cannot make her legs longer, although she tries hard. Her days fi lled with exercise are filmed in long, static shots. There is no joy or enthusiasm. Sweat and tiredness are a part of strenuous exercise. Alla does not spin on a roof, nor does she jump rhythmically while cooking, like the characters of First Position and Only When I Dance. There is nothing from a fairy tale or Hollywood in her experiences. Additionally, Skalski’s fi lm breaks the myth of the dancer’s body being strong and inexhaustible. This is how we traditionally look at ballet, where there is no place for showing weakness.